The current (speculative) police literature - Lemo, Matías (Tropelías: Review of Literary Theory and Comparative Literature, 2022)
We propose a brief review of the evolution of the detective genre in Argentina, by the typical typology of the police, by its current peculiarities in relation to what we call here “realistic data”, the notion of “border” and speculative literature. We take these in consideration, together with the reading of Los que duermen en el polvo by Horacio Convertini (2016) to try to understand how the current police call is marked by ambiguity and a clear problematization of it’s present of enunciation due to Nueva Narrativa Argentina Especulativainfluence.